A minimum of 15% semi-natural habitat facilitates adequate wild pollinator visitation to a pollinator-dependent crop. (February 2023) - Eeraerts, Maxime
Abstract: The continued expansion of pollinator-dependent crops increases our reliance on insect pollinators, with wild pollinators providing a considerable proportion of pollination services depending on the crop and landscape context. To ensure pollination services delivered by wild pollinators, it is suggested to conserve semi-natural habitat (SNH) in agricultural landscapes. However, quantitative thresholds of the required amount of SNH to inform policy and farmers are lacking. This study assessed how non-linear models can predict the relationship between wild pollinator visitation and SNH near sweet cherry orchards in Belgium. In addition, I determined a threshold of the required amount of SNH to support pollinator visitation. The relationship between total wild pollinator visitation, bumble bee visitation, solitary bee visitation and wild pollinator richness was best predicted by a non-linear relationship with the proportion of SNH within 250 m around the fields. This study provides empirical evidence on the benefit of using non-linear models to increase our understanding between landscape structure and pollinator visitation. 15% of SNH is the estimated threshold beyond which pollinator visitation did not increase any further. Increasing the amount of SNH to 15%, if it is below this threshold, is recommended to enhance crop pollination in this specific system and region. Conservation of SNH at higher levels than 15% should be maintained for biodiversity conservation and ecosystem functioning. Highlights: The relation between landscape and pollinators was studied with non-linear models. Pollinator visitation increases non-linear with the amount of semi-natural habitat. 15 % semi-natural habitat was identified as minimum to ensure pollinator visitation.